Educação Especial: inclusão de Alunos Autistas no ensino regular - SOARES, Ana Cláudia Duarte (Universidade Federal do Tocantins, 2021)
The inclusion of children with special needs, such as the autistic, in regular schools has been a subject of study and at the same time a challenge for educational institutions and teachers, especially when it comes to public schools. In this sense, this work started from the need to identify inclusion practices, both in the theoretical references already published, and in the State School Diolindo dos Santos Freire, located in the city of Novo Alegre, Tocantins, which was the site of field research of this monograph. Autism, like other special needs, is often treated as a serious illness, so educational institutions treat children with these needs in a welfare-oriented way and only need to be approved at the end of the school year without taking into account their rights and proper care as with other children. From a theoretical point of view, this research goes through the analysis of autistic rights under the light of educational legislation, the types of autism present in society in general, as well as the levels and degrees of autism and their characteristics. The study also addresses subjects about teacher education as an essential element to work with children with autism and other specialties, because teachers need to be prepared, given the demands present in schools and not always the initial training of professionals is sufficient to to attend to the peculiarities of the children and, consequently, to include them in the regular classes and in the school community itself. The result of this work brings important information about the daily life of autistic children, as well as practices already existing at school to guide families and their own children and insert them in society.